Use of agile methods and practices in the Philippines - Sison, Raymund (Animo Repository, 2007)
Agile methods are increasingly gaining attention in many developed countries; however, there is a dearth of empirical studies showing their successful use in developing nations. This needs to be addressed because most software offshore outsourcing destinations are in the developing world. This paper describes experiences in the use of agile methods and practices by software development firms in the Philippines, a developing country that has consistently appeared in lists of top software outsourcing destinations. The results tend to confirm those found in the literature concerning the positive impact of agile methods on software development, and how software organizations tend to adapt agile practices to suit their own organizational and project contexts. One case study in this paper also describes a particular approach to agile offshore software development. © 2007 IEEE.